Modeling the Dynamic Relationship between Inflation, Oil Price, and Macroeconomic Variables: Evidence from Saudi Arabia - Elsharif, Mohamed Sharif Bashir; Elamin, Ahlam Abdelhadi Hassan (International Journal of Energy Economics and Policy, 2025)
This paper investigates the dynamic relationship between inflation, economic growth, oil price, money supply, and current account in Saudi Arabia for the period 1980–2023. It employs the autoregressive distributed lag (ARDL) approach and error correction model (ECM) to examine the short-run and long-run dynamics. The bounds test of cointegration analysis confirms the existence of a long-term relationship between targeted variables. The ARDL model estimates suggested that gross domestic product (GDP), oil price, and money supply are negatively related to inflation. They also indicated that current accounts have a positive effect on price levels, GDP, and money supply, and a negative effect on oil prices and inflation levels. Therefore, enhancing regulatory quality and mobilizing more domestic resources can reduce inflation and accelerate economic growth.